Supreme Court decisions - Croy, Anita (Inside American politics., 2019)
Describes the history and origins of the United States Supreme Court, discussing how justices are appointed, the impact of its rulings, the role of the court today, and current controversies. Includes photographs, side bars, critical thinking questions, a glossary, and resources for further information.